Análise dos programas de atividade física dos municípios pertencentes à Microrregião de Saúde de Uberaba - PIRES, Marijunio Rocha (2016)
The literature shows a growing number of Physical Activity Programs (PAFs) in the Brazilian public service, demonstrating concern by managers to reduce the health risks related to physical inactivity. Some studies were conducted by the researchers aiming to verify the effectiveness of these programs. However, the characteristics of many PAFs are still unknown. The objectives of this study were to identify and describe the features of Physical Activity Programs and to elaborate the profile of the appliers of these programs in the Health Micro-region of the municipalities of Uberaba, MG. It is a cross-sectional study performed in eight municipalities of this micro-region. The eligible people for the study consisted of 89 individuals, as follows: Municipal Health Departments (N=8), Social Action (N=8), Sport/Leisure (N=8), PAFs Coordinators (N=14) and Appliers (N=51). The subjects answered a standardized questionnaire withsocio-demographic questions and related to resources, activities, expected results and professionals involved in PAFs. Absolute and relative frequenciesdistributions, average and standard deviation of the variables studiedwere calculated. The results showed sixteenPAFsin the micro-region. The evaluation of the eleven eligible programs showed higher proportion of linked PAFs to the Health Departments (54.5%), predominantly working in outdoor gyms, squares/parks (72.7%). The main target people were the elderly people (100.0%), predominant risk group of diabetic/hypertensive (100.0%) and the main long-term expected results was the medium and high complexity treatment costs decrease (81.8%). Among the appliers, most of them have higher education (88.6%) with Physical Education degrees (63.6%). Physiotherapists were more present in Health Departments (90.0%), and professionals of physical education were in the Departments of Sport/Leisure (60.7%). Most of them worked 20 hours per week and received two minimum wages per month. Based on the results, PAFs in all analyzed municipalities were observed with a resource supply, activity and applicators with higher education and Physical Education degree. However, investment in continuing education, PAF management participation, expansion of physical assessments and integration of physical education professionals in PAFs related to the Health Departments are still gaps to be filled.